الإكثار الدقيق لنبات Diantus caryophll - العذبة حسين; رشيد عهد (Latakia University Journal -Biological Sciences Series, 2018)
The aim of the study was to examine shoots (1-2cm) containing (shoot tips and node segments) which were excised and surface – disinfected , they were cultured on MS ( Murashige and Skoog 1962) , then placed onto based medium containing a combination of growth regulators at different concentrations (BAP, NAA, GA3) . After that they were placed into MS based medium containing NAA at different concentrations. Result showed that the highest number of growth was 39.6 when (1.33µM BAP+1 µMNAA) were adding , while the highest of the growth was 5.1 cm in medium MS5 after adding ((1.33µM BAP+1 µMNAA+2.4 µM GA3) . The observed rooting was (6.9 root,5.7cm length and %64 in percentage of rooting ) in R3 (MS+ 7.33 µMNAA) . Acclimatized plants grow well under greenhouse condition( %85) . لقد تم تطوير تقنية لإكثار نبات القرنفل المعمر Diantus caryophll مخبريا بمعدل إكثار مرتفع بواسطة تقنية زراعة الأنسجة النباتية بدأ من أفرع بطول ( 1-2) سم وتحتوي على العقد والقمم النامية . والتي زرعت في أنابيب أختبار تحوي وسطا مغذيا MS (Murashige and Skoog 1962) وبعد ذلك أ كثرت على وسط MS مضاف إليه منظمات نمو مختلفة (أمينو بيورين PAB , ونفثالين أسيتك أسيد NAA , والجبريلين GA3) و ثم زرعت النموات الخضرية الناتجة على وسط MS يحتوي تراكيز مختلفة من NAA من أجل تجذيرها , أوضحت النتائج تشكل أكبر عدد للنموات 39.6 في المعاملة MS3 التي تحتوي1.33 µM من BAP و 1µM NAA. في حين لوحظ أكبر طول للنموات 5.1 سم في المعاملة MS5 التي تحتوي GA3 2.4µM+1.33µMBAP+1µMNAA . أما في مرحلة التجذير فكانت للمعاملة R3 التي تحتوي MS+7.3µMNAA القضلى . إذ كانت نسبة التجذير %64 وعدد الجذور %6.9 , أما طولها فكان 5.7 سم وكانت الأقلمة %85 .